Type I Interferon Regulates the Survival and Functionality of B Cells in Rainbow Trout - Benedicenti, Ottavia; Wang, Tiehui; Morel, Esther; Secombes, Christopher J.; Soleto, Irene; Díaz-Rosales, Patricia; Tafalla, Carolina (Frontiers in Immunology, 2020)
Interferons (IFNs) orchestrate antiviral responses in jawed vertebrates and can be classified into three types based on different aspects of their genomic organization, structure and receptors through which they signal and function. Generally, type I and type III IFNs include cytokines that directly induce an antiviral response, whereas type II IFNs are well known for their immunomodulatory role during viral infections. In mammals, type I IFNs have been shown to also regulate many aspects of B cell development and differentiation. Yet, these functions have been only faintly investigated for teleost IFNs. Thus, in the current study, we have examined the effects of a model type I rainbow trout IFN molecule (IFNa) on blood naïve (IgM+IgD+) B cells, comparing them to those exerted by type II IFN (IFN). Our results demonstrate that IFNa increases the survival of naïve rainbow trout B cells, in the absence of lymphoproliferative effects, by rescuing them from spontaneous apoptosis. Additionally, IFNa increased the phagocytic capacity of blood IgM+IgD+ B cells and augmented the number of IgM-secreting cells in blood leukocyte cultures. IFN, on the other hand, had only minor effects up-regulating IgM secretion, whereas it increased the phagocytic capacity of IgM- cells in the cultures. Finally, given the recent identification of 9 mx genes in rainbow trout, we have also established which of these genes were transcriptionally regulated in blood naïve B cells in response to IFNa. This study points to a previously undescribed role for teleost type I IFNs in the regulation of B cell responses.